The Strategy - Ending Globalization Disorders - Yunus Lubega Butanaziba (Interdisciplinary Description of Complex Systems, 2010)
Scientifically, globalization is a pure-form or model that refers to a condition whereby a dominant state unilaterally or multilaterally maintains a balance of power to fail member states in the international system it dominates. Globalization can be implemented exclusively or inclusively under blocs (regional) or International Governmental Organizations (IGOs) as means of the balance of power for the failure of states. This is the theme that this article pursues to objectively examine the current globalization regime as the function of two arms of the balance of power applied to fail states in the international system. One arm of the current globalization regime applies interest-lending of the Bretton Woods institutions namely, International Bank for Reconstruction (IBRD)/World Bank and International Monetary Fund (IMF). The other arm uses the strategy of resource wars. The problem is that interest charges of the World Bank and IMF have failed to cause real domestic growth in 185 states since the initial Ten/Five-year Development Plans, 1946/51-56. This is seen in the domestic and foreign debt burdens arising out of loan interests of the IBRD/World Bank and IMF. There have been more than 136 resource wars that have caused over250 million deaths (market value loss of over USD 500 trillion) in the period 1946 to date. The unit of analysis of the paper is that the previous and current strategies of globalization have been illegitimate, severely violated fundamental human right, contravened business ethics and caused the failure states. Thus, the Bretton Woods system has not, and will not as it stands, benefit USA and her allied member states and the Third World inclusive.Legally and morally, Latin American states who signed the Bretton Woods Agreements in 1944 were not in-due-form: African, Asian and Eastern European states were not represented; and given the most compelling fact that others from Europe (e.g. Germany) and Japan agreed in the unique historical moment, the logical conclusion is that the liberty and fundamental freedoms and rights of member states have since been violated by the IBRD/World Bank and IMF interest-lending. (i) The paper recommends among others a new formula for the re-creation a humanistic international monetary authority that will benefit all stakeholders without interfering in the balance of power. To say the least, interest lending of the Bretton Woods systems was appropriated from the 1545 Act (“An Acte Agaynst Usurie”, 37 H.viii 9), which must be replaced with the humanistic monetary formula that maintains the balance of power to the lender, and also agreeable with international business ethics and human rights. (ii) This will multiply earnings of the world bank group to over 150 %. (iii) Over 3 billion out of the 6,8 billion people who had abandoned or feared interest-lending of commercial banks will join the industry – hence pulling over 150 % earnings. (iv) Employment will increase to more than 60 %. (v) Inflation will fall to 3 %. (vi) Local and investor confidence will rise, hence enlarging the financial market. (vii) There is urgent need for creating new geographies of the peace by closing Western driven ethnic battle frontlines that emerged with Huntington’s new pattern of conflict (1990s to date).